TOTAL QUALITY MANAGEMENT AND ORGANIZATIONAL RESILIENCE: A THEORETICAL SERMON (American Journal of Business Management, Economics and Banking, 2024)
High operating challenges affecting shipping companies in Rivers State, Nigeria specifically came from neglect on total quality management (TQM). Most of the managers use few workers that are friendly and loyal to function instead of involving the skillful, experienced employees to be resilient against any unforeseen circumstances in the business. Organizations that realized the necessities of applying the measures of total quality management could attract profitability and resilience to withstand pressures or competitiveness. The study investigated total quality management and organizational resilience. The main sermon was on shipping companies in Rivers State, Nigeria. The researcher concluded that successful implementation of total quality management using employee involvement could lead to robustness and agility of the firm.